Multivalent dendritic polyglycerolamine with arginine and histidine end groups for efficient siRNA transfection - Sheikhi Mehrabadi, Fatemeh; Zeng, Hanxiang; Johnson, Mark; Schlesener, Cathleen; Guan, Zhibin; Haag, Rainer (Beilstein Journal of Organic Chemistry, 2015)
The success of siRNA-based therapeutics highly depends on a safe and efficient delivery of siRNA into the cytosol. In this study, we post-modified the primary amines on dendritic polyglycerolamine (dPG-NH2) with different ratios of two relevant amino acids, namely, arginine (Arg) and histidine (His). To investigate the effects from introducing Arg and His to dPG, the resulting polyplexes of amino acid functionalized dPG-NH2s (AAdPGs)/siRNA were evaluated regarding cytotoxicity, transfection efficiency, and cellular uptake. Among AAdPGs, an optimal vector with (1:3) Arg to His ratio, showed efficient siRNA transfection with minimal cytotoxicity (cell viability ≥ 90%) in NIH 3T3 cells line. We also demonstrated that the cytotoxicity of dPG-NH2 decreased as a result of amino acid functionalization. While the incorporation of both cationic (Arg) and pH-responsive residues (His) are important for safe and efficient siRNA transfection, this study indicates that AAdPGs containing higher degrees of His display lower cytotoxicity and more efficient endosomal escape.
Keywords: arginine; dendritic polyglycerolamine; histidine; multivalent vector; siRNA delivery